Data from: Evolution and origin of sympatric shallow-water morphotypes of Lake Trout, Salvelinus namaycush, in Canada's Great Bear Lake - Harris, Les N.; Chavarie, Louise; Bajno, Robert; Howland, Kimberly L.; Wiley, Simon H.; Tonn, William M.; Taylor, Eric B. (Zenodo, 2014)
Range expansion in north-temperate fishes subsequent to the retreat of the Wisconsinan glaciers has resulted in the rapid colonization of previously unexploited, heterogeneous habitats and, in many situations, secondary contact among conspecific lineages that were once previously isolated. Such ecological opportunity coupled with reduced competition likely promoted morphological and genetic differentiation within and among post-glacial fish populations. Discrete morphological forms existing in sympatry, for example, have now been described in many species, yet few studies have directly assessed the association between morphological and genetic variation. Morphotypes of Lake Trout, Salvelinus namaycush, are found in several large-lake systems including Great Bear Lake (GBL), Northwest Territories, Canada, where several shallow-water forms are known. Here, we assess microsatellite and mitochondrial DNA variation among four morphotypes of Lake Trout from the five distinct arms of GBL, and also from locations outside of this system to evaluate several hypotheses concerning the evolution of morphological variation in this species. Our data indicate that morphotypes of Lake Trout from GBL are genetically differentiated from one another, yet the morphotypes are still genetically more similar to one another compared with populations from outside of this system. Furthermore, our data suggest that Lake Trout colonized GBL following dispersal from a single glacial refugium (the Mississippian) and support an intra-lake model of divergence. Overall, our study provides insights into the origins of morphological and genetic variation in post-glacial populations of fishes and provides benchmarks important for monitoring Lake Trout biodiversity in a region thought to be disproportionately susceptible to impacts from climate change. Genepop Data File Genepop data file (3 digit format) used for analyses - sample codes are listed in Table 1 of the manuscript. Genepop 3Dig - All Samples